Pedagogical case study of Technology-Based Learning (TBL) innovation practices from the perspective of the Kurikulum Merdeka - Rukiah Rukiah (Himpunan Pengembang Kurikulum Indonesia, 2026)
A pedagogical case study on the implementation of innovative learning practices within the Kurikulum Merdeka perspective at the elementary school level is important for examining the potential, challenges, and effective implementation strategies. The purpose of this study is to identify the potential, challenges, and effective implementation strategies. This study uses a qualitative case study approach to investigate in depth the implementation of innovative learning practices within the Kurikulum Merdeka context at the elementary school level. Data were collected through classroom observations, in-depth interviews with teachers, principals, and students, and analysis of curriculum documents and lesson plans. Data analysis was conducted inductively to identify key themes, potential challenges, and effective implementation strategies based on the perspectives of school stakeholders. The implementation of Technology-Based Learning (TBL) is becoming an important element in the teaching and learning process. However, several challenges remain, such as limited infrastructure and varying teacher proficiency with technology. This study shows that the application of technology in the learning process significantly increases student motivation, engagement, and understanding of the material. The principles of the Kurikulum Merdeka emphasize the importance of independent and creative learning. However, technical constraints and teacher readiness remain major challenges that require serious attention in the future. Abstrak Studi kasus pedagogik tentang penerapan praktik pembelajaran inovatif dalam perspektif Kurikulum Merdeka di tingkat sekolah dasar menjadi penting untuk dikaji guna memahami potensi, tantangan, serta strategi implementasi yang efektif. Tujuan penelitian ini adalah untuk mengidentifikasi potensi, tantangan, serta strategi implementasi yang efektif. Penelitian ini menggunakan pendekatan studi kasus kualitatif untuk menyelidiki secara mendalam penerapan praktik pembelajaran inovatif dalam konteks Kurikulum Merdeka di tingkat sekolah dasar. Data dikumpulkan melalui observasi di kelas, wawancara mendalam dengan guru, kepala sekolah, dan murid, serta analisis dokumen kurikulum dan rencana pembelajaran. Analisis data dilakukan secara induktif untuk mengidentifikasi tema-tema utama, potensi, tantangan, serta strategi implementasi yang efektif berdasarkan perspektif para pemangku kepentingan di sekolah. Penerapan Technology-Based Learning (TBL) telah mulai menjadi elemen penting dalam proses belajar mengajar. Namun, masih terdapat beberapa tantangan, seperti keterbatasan infrastruktur dan beragamnya kemampuan guru dalam mengoperasikan teknologi. Penelitian ini menunjukkan bahwa penerapan teknologi dalam proses pembelajaran secara signifikan meningkatkan motivasi, keterlibatan, dan pemahaman murid terhadap materi. Prinsip Kurikulum Merdeka menekankan pentingnya pembelajaran yang mandiri dan kreatif. Namun, kendala teknis dan kesiapan guru masih menjadi tantangan utama yang perlu mendapat perhatian serius di masa depan. Kata Kunci: Kurikulum Merdeka; sekolah dasar; TBL; technology-based leaning